MULTIKURALISME PELAJAR NU DI SMA MUHAMMADIYAH WONOSOBO - Rizal Rifa’i; Khoiru Alfatul Huda; Nurul Mubin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to analyze the forms of multiculturalism developed among Nahdlatul Ulama (NU) students at Muhammadiyah High School in Wonosobo. Multiculturalism, as a paradigm of cultural diversity, is essential for fostering social harmony in a pluralistic society. This research employs a qualitative approach with a case study method to explore the dynamics of NU students' interactions within an educational environment rooted in Muhammadiyah values and Islamic teachings.The findings reveal that NU students at Muhammadiyah High School in Wonosobo demonstrate inclusive attitudes, tolerance, and mutual respect for differences in religious, social, and cultural aspects. Key factors supporting the realization of this multiculturalism include a school environment that encourages intergroup dialogue, the teaching of moderate Islamic values, and the influence of NU traditions emphasizing the importance of tasamuh (tolerance). However, the study also identifies challenges such as stereotypes between groups and a lack of deep understanding of other cultures, which necessitate a more integrated multicultural education approach.Thus, this study asserts that multiculturalism among NU students at Muhammadiyah High School in Wonosobo not only serves as a means to foster harmonious relationships but also as a crucial foundation for strengthening national identity based on diversity.